2021
DOI: 10.1007/s40544-021-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nano-topography and tribochemistry of ZDDP tribofilms from variations in contact configuration with steel and DLC surfaces

Abstract: In this work, we evaluated the effect of the counter-body material (the same or dissimilar) and contact configuration (moving or stationary body), at similar contact tribological conditions, on the tribochemical and nanotopography characteristics of adsorbed surface films. Zinc dialkyldithiophosphate (ZDDP), the best performing anti-wear additive, was used in self-mated steel/steel and DLC/DLC contacts, which were compared with mixed steel/DLC and DLC/steel contacts in 1-h and 6-h sliding tests. The macroscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Figure 1b illustrates the FTIR spectrum of CuDDP, with distinct C-H characteristic peaks (including CH 3 and CH 2 ) at 1380 cm −1 . Pertinent to this study are two pronounced absorption peaks near 1000 cm −1 , attributed to P-O-C at 636 cm −1 and P=S, indicative of the HDDP modifier's presence [27,28]. Figure 1c displays a TEM image and particle size distribution of CuDDP, revealing that the nanoparticles are spherical with an average diameter of approximately 5 nm, as shown in Figure 1d.…”
Section: Characterization Of Cuddpmentioning
confidence: 51%
“…Figure 1b illustrates the FTIR spectrum of CuDDP, with distinct C-H characteristic peaks (including CH 3 and CH 2 ) at 1380 cm −1 . Pertinent to this study are two pronounced absorption peaks near 1000 cm −1 , attributed to P-O-C at 636 cm −1 and P=S, indicative of the HDDP modifier's presence [27,28]. Figure 1c displays a TEM image and particle size distribution of CuDDP, revealing that the nanoparticles are spherical with an average diameter of approximately 5 nm, as shown in Figure 1d.…”
Section: Characterization Of Cuddpmentioning
confidence: 51%
“…Their findings are consistent with our experimental results. In addition, high friction of the ZDDP tribofilms is confirmed at the macroscale [12,21], regardless of the sliding pair. For example, the DLC/DLC and Si3N4/steel pairs.…”
Section: Assumption Of Shear Strength On Zddp Tribofilmmentioning
confidence: 77%
“…We confirmed that there was a significant difference in shear strength between the steel and ZDDP tribofilm. Therefore, we assumed that the increase in friction force by the ZDDP tribofilm was caused by the [12,15,21]. Generally, the metal/metal friction is much higher, as reported by Bowden and Tayber [24].…”
Section: Assumption Of Shear Strength On Zddp Tribofilmmentioning
confidence: 93%
See 1 more Smart Citation
“…Umer [25] reported that the nano-friction of the ZDDP tribofilm formed during the macro sliding test is higher than that of the no-worn steel surface. In addition, the high friction behavior of the ZDDP tribofilm has been consistently observed at the macroscale, irrespective of the sliding pair [18,26]. Kaisei Sato [27] utilized in situ Atomic Force Microscopy (AFM) to investigate the mechanism behind this high friction.…”
Section: Introductionmentioning
confidence: 99%